Global and precise identification of functional miRNA targets in mESCs by integrative analysis. (28th July 2022) - Schaefer, Moritz; Nabih, Amena; Spies, Daniel; Hermes, Victoria; Bodak, Maxime; Wischnewski, Harry; Stalder, Patrick; Ngondo, Richard Patryk; Liechti, Luz Angelica; Sajic, Tatjana; Aebersold, Ruedi; Gatfield, David; et al.
Abstract: MicroRNA (miRNA) loaded Argonaute (AGO) complexes regulate gene expression via direct base pairing with their mRNA targets. Previous works suggest that up to 60% of mammalian transcripts might be subject to miRNA‐mediated regulation, but it remains largely unknown which fraction of these interactions are functional in a specific cellular context. Here, we integrate transcriptome data from a set of miRNA‐depleted mouse embryonic stem cell (mESC) lines with published miRNA interaction predictions and AGO‐binding profiles. Using this integrative approach, combined with molecular validation data, we present evidence that < 10% of expressed genes are functionally and directly regulated by miRNAs in mESCs. In addition, analyses of the stem cell‐specific miR‐290‐295 cluster target genes identify TFAP4 as an important transcription factor for early development. The extensive datasets developed in this study will support the development of improved predictive models for miRNA‐mRNA functional interactions. Synopsis: Integrative analysis of transcriptome data from miRNA‐depleted mESC lines, miRNA interaction predictions and AGO‐binding profiles allows for the identification of direct and functional miRNA targets. These data support the development of algorithms to predict functional miRNA‐mRNA interactions. Less than 10% of transcribed genes in mESCs show evidence for direct and functional regulation by miRNAs. TFAP4 is regulated by miRNAs in mESCs and plays an important role in the regulation of gene expression. Depletion of Tfap4 in Drosha _KO mESCs is not sufficient to rescue global miRNA phenotypes. Abstract : Integrative analysis of transcriptome data from miRNA‐depleted mESC lines, miRNA interaction predictions and AGO‐binding profiles allows forthe identification of direct and functional miRNA targets. These data support the development of algorithms to predict functional miRNA‐mRNA interactions.